Today and Future of Culturally Responsive Teaching (CRT) : Indonesia Needs It - Patras, Yuyun Elizabeth; Rahmawati, Yuli; Japar, Muhammad; Hidayat, Rais (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to describe the future of Culturally Responsive Teaching (CRT) research and publication by looking at trends, countries, institutions, authors, and hotspots in education. This research method uses a literature review with a flow of gathering, filtering, bibliometric, mapping, and reviewing data sources from the Scopus index database amounting to 222 documents. This study uses data analysis based on the Vosviewer software. The study's findings showed that the trend of Culturally Responsive Teaching (CRT) research continues to grow. Globalization and the advancement of communication technology encourage teachers to develop teaching skills using CRT-oriented pedagogics. The concept and implementation of CRT in learning are still dominated by the most productive countries, organizations, and figures in the United States. This is a challenge for any country, especially Indonesia, which is multicultural. To increase research and publications in the field of CRT, the increase in teachers' awareness of cultural, ethnic, and racial diversity, Mastery of various multimodal teaching, and taking teaching resources from the local cultural context require serious attention together. The hotspots that can be done for future CRT research are directed at terms or variables that have not been explored much, such as pre-service teacher, self-efficacy, CRT practice, impact, STEM, class, instruction, disability, work, equity, implementation, and technology.